LEVEL OF PATIENT SATISFACTION WITH SERVICE NURSING IN THE INSTITUTION UNIT [TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KEPERAWATAN DI UNIT RAWAT INAP] - Omy Oini; Renata Komalasari; Shinta Yuliana Hasibuan (Nursing Current: Jurnal Keperawatan, 2019)
Patient satisfaction is one of the factors that can be used as a reference in improving quality services in health services in hospitals. Nursing care is one area of service in the hospitals. Patient's satisfaction with nursing care in a hospital is important in providing an overall picture of the quality of health care, particularly in the inpatient ward. In a private hospital in West Jakarta area, there has never been a study of patient satisfaction of nursing service, particularly in the inpatient unit. The purpose of this study was to explore the level of patient satisfaction with the nursing service in the inpatient unit at a private hospital in West Jakarta. Aspects being investigated consisted of tangibility, reliability, responsiveness, assurance, and empathy. This research was a quantitative descriptive research with 135 respondents of inpatient patients obtained by purposive sampling technique. Inclusion criteria included patients who were hospitalized for at least three days, age of 18 years old and over, ability to read and write in Indonesian, and willing to be respondents. The instrument used was the Quality Service (SERQUAL) questionnaire that has been tested for its validity and realibility. Data was analyzed using descriptive univariate analysis. The results showed that the level of patient satisfaction of the nursing service on tangible was 39.3%, reliability was 57.8%, responsiveness was 54.8%, assurance was 56.3%, and empathy was 64.4.%. Future study should examine the relationship between patient satisfaction levels and nursing care based on these five aspects. The hospital may use data from this study as a baseline in efforts to improve nursing service quality for patients. BAHASA INDONESIA ABSTRAK Kepuasan pasien merupakan salah satu faktor yang dapat dijadikan acuan dalam meningkatkan pelayanan berkualitas dalam pelayanan kesehatan di rumah sakit. Salah satu bidang layanan di rumah sakit adalah layanan keperawatan. Kepuasan pasien terhadap asuhan keperawatan di sebuah rumah sakit penting dalam memberikan gambaran keseluruhan tentang kualitas pelayanan kesehatan di sebuah sakit, khususnya di ruang rawat inap. Di sebuah rumah sakit swasta di wilayah Jakarta Barat belum pernah dilakukan penelitian tingkat kepuasan pasien di unit rawat inap terhadap layanan keperawatan. Tujuan penelitian ini adalah menggali tingkat kepuasan pasien terhadap pelayanan keperawatan di unit rawat inap di sebuah rumah sakit swasta di wilayah Jakarta Barat. Aspek yang dikaji meliputi aspek tangible, reliability, responsiveness, assurance, dan empathy. Penelitian merupakan penelitian deskriptif kuantitatif dengan responden penelitian 135 pasien rawat inap yang diperoleh dengan teknik menggunakan purposive sampling. Kriteria inklusi yaitu pasien yang dirawat di unit rawat inap minimal 3 hari, pasien berusia minimal 18 tahun, pasien dapat baca tulis dalam Bahasa Indonesia, dan bersedia menjadi responden. Instrumen yang digunakan adalah kuesioner ServiceQuality (SERQUAL) yang sudah diuji validitas dan reabilitasnya, mencakup domain tangible, reliability, responsiveness, assurance, dan empathy. Data dianalisis menggunakan analisis univariat deskriptif. Hasil dari penelitian menunjukan tingkat kepuasan pasien terhadap pelayanan keperawatan pada dimensi tangible adalah 39.3%, reliability 57.8%, responsiveness 54.8%, assurance 56.3%, empathy 64.4.%. Penelitian selanjutnya perlu mengkaji hubungan antara tingkat kepuasan pasien dan pelayanan keperawatan berdasarkan kelima aspek tersebut. Rumah sakit dapat menggunakan hasil penelitian ini sebagai data dasar dalam upaya meningkatkan kualitas pelayanan keperawatan di rumah sakit.